Effect of bioinoculants on soil fertility, phosphate solubilization, and yield enhancement in chickpea (Cicer arietinum) under field conditions - Tomer, Supriya; Khati, Priyanka; Chandra, Ramesh; Bhandari, Narendra Singh; Gangola, Saurabh; Singh, Jitender (Edelweiss Applied Science and Technology, 2026)
This study evaluates the effectiveness of three phosphate-solubilizing bacteria (PSB): Lysinibacillus macrolides (ST-30), Bacillus cereus (ST-06), and Pseudomonas pelleroniana (N-26), in enhancing soil phosphorus (P) availability, improving chickpea (Cicer arietinum PG-186) yield, and optimizing crop economics compared to chemical P-fertilizer. The application of PSB strains significantly increased soil available phosphorus (AP) and nitrogen content. The highest soil P content, with an 89.89% increase over pre-sown soil, and maximum grain yield, at 24.98 q/ha (a 37.57% increase over control), were achieved with the ST-30 strain combined with 20 kg P2O5/ha. PSB, especially Lysinibacillus macrolides ST-30, proved highly effective, demonstrating superior performance in P-solubilization and yield enhancement compared to chemical fertilizers alone. Integrating PSB ST-30 with 20 kg P2O5/ha resulted in the highest net profit of INR 45,453 and the best cost-benefit ratio of 108%, offering a sustainable and economically advantageous alternative to standard chemical fertilization. Notably, the treatment involving PSB ST-30 with 20 kg P2O5/ha achieved the highest harvest index of 55.71, comparable to N-26 with 20 kg P2O5/ha. These findings suggest that the bioinoculants studied could serve as effective, sustainable alternatives to chemical fertilizers, improving soil health and crop productivity.